2014
DOI: 10.1039/c4tb00522h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mesenchymal stem cell response using uniaxially stretched poly(ε-caprolactone) film micropatterns for vascular tissue engineering application

Abstract: Regeneration of tunica media with anisotropic architecture still remains a challenging issue for vascular tissue engineering (TE). Herein, we present the development of flexible poly(3-caprolactone) (PCL) film micropatterns to regulate mesenchymal stem cells (MSCs) function for tunica media construction.Results showed that uniaxial thermal stretching of PCL films resulted in topographical micropatterns comprising of ridges/grooves, and improved mechanical properties, including yield stress, Young's modulus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
(130 reference statements)
0
55
1
Order By: Relevance
“…The elicitation of cellular elongation during direct mechanotransduction could cause aligned cytoskeletonal fibers to trigger nucleus deformation. Such nucleus deformation would further lead to the structural adjustment of the DNA and nucleus pores, and the accessibility of transcriptional factors would be changed, resulting in alteration of gene expression . Our observations indicated that the orientated E‐jetted fibers had contributions to cell elongation, and gene expression toward tendon tissue through such mechanotransduction pathways, which suggested that the as‐fabricated scaffold has potential for tendon regeneration.…”
Section: Discussionmentioning
confidence: 78%
“…The elicitation of cellular elongation during direct mechanotransduction could cause aligned cytoskeletonal fibers to trigger nucleus deformation. Such nucleus deformation would further lead to the structural adjustment of the DNA and nucleus pores, and the accessibility of transcriptional factors would be changed, resulting in alteration of gene expression . Our observations indicated that the orientated E‐jetted fibers had contributions to cell elongation, and gene expression toward tendon tissue through such mechanotransduction pathways, which suggested that the as‐fabricated scaffold has potential for tendon regeneration.…”
Section: Discussionmentioning
confidence: 78%
“…Results in this study also demonstrated that the tenocytes elongated in a direction which was parallel to the geometric cures. The cellular alignment and elongation induced from the geometric cures further enhanced the expression levels of tendious genes via the mechanotransduction pathway …”
Section: Discussionmentioning
confidence: 99%
“…These approaches have involved biomaterials that utilize both chemical [4042] and topographical modifications [43, 44] to regulate smooth muscle cells (SMCs) over-proliferation and enhance ECM synthesis as well as other innovative biomaterials that are impregnated with stem cells and/or utilize biomechanical stimulation to improve overall biocompatibility [41, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as transforming growth factor (TGF-β1) have also been conjugated to fibrin hydrogel vascular grafts and exposed to mechanical stimulation [41] to improve mechanical properties and ECM content. Mechanical stimulation has also been combined with mesenchymal stem cells (MSCs) cultured on micropatterned poly(e-caprolactone) films for improved functionally of SMCs [45]. Another study electrospun a larger pore and thicker polycaprolactone (PCL) fiber to construct vascular grafts that demonstrated immunomodulatory properties resulting in vascular regeneration [43].…”
Section: Discussionmentioning
confidence: 99%